KUAT BENDING, FRAKTOGRAFI, DAN STRUKTUR MIKRO HASIL 3D PRINTING BERBAHAN PLA (POLYLACTIC ACID) - TITANIUM - Darsin, Mahros; Ismono, Firman Ema; Asrofi, Mochamad; Hermawan , Yuni; Hardiatama , Intan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Manufacturing technology has experienced significant progress with various innovations, including 3D printing. In this study, an innovation was made using a filament made of PLA 60% and titanium 40%. Bending tests are carried out to determine the combination of 3D printing parameters that can produce the most optimal bending strength. This study uses the Taguchi method orthogonal matrix L4(23). The data is processed using Analysis of Variance (ANOVA). The parameters that produce optimal bending strength values are a nozzle temperature of 230 ⁰C, a print speed of 20 mm/s, and a layer height of 0.3 mm, with the highest bending strength value of 7.13 MPa and the lowest of 2.16 MPa. The factors that contributed significantly to the bending strength results were nozzle temperature of 52.84 %, print speed of 15.91 %, and layer height of 1.80 %.